1999
DOI: 10.1097/00063198-199901000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of inner-city asthma

Abstract: Racial and ethnic minorities of low socioeconomic status residing in urban environments currently referred to as inner cities appear to represent a population that is disproportionately at high risk for asthma morbidity and mortality. Epidemiologic studies suggest that key risk factors contributing to asthma morbidity within the inner city include social demography, the physical environment (indoor and outdoor), and health care access and quality. This epidemiologic literature has helped to define opportunitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…[7][8][9][10][11][12][13] This study showed an association between asthma symptoms and behavioral comorbidity, and a large proportion of children with persistent symptoms experienced behavioral problems across several domains. The combined burden of asthma, behavioral difficulties, and poverty likely has an impact on the quality of life of these children and families.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13] This study showed an association between asthma symptoms and behavioral comorbidity, and a large proportion of children with persistent symptoms experienced behavioral problems across several domains. The combined burden of asthma, behavioral difficulties, and poverty likely has an impact on the quality of life of these children and families.…”
Section: Discussionmentioning
confidence: 65%
“…[4][5][6] In the United States, impoverished children and children from minority ethnic and racial backgrounds suffer disproportionately from asthma. [7][8][9][10][11][12][13] The morbidity associated with asthma is extensive and includes emergency department visits, 6,14,15 hospitalizations, 4,5,16 and cost, 17,18 as well as less traditional factors, including impaired quality of life 19 and absenteeism. 20 In addition, co-existing medical conditions [21][22][23] as well as psychiatric conditions 24,25 now are considered issues that both children and adults with asthma face.…”
mentioning
confidence: 99%
“…24 Asthma in inner-city and rural populations is often regarded differently based on the fact that the underlying etiologies and environmental exposures may vary to some degree. 25,26 However, both populations face similar challenges in terms of multiple barriers to adequate health care including poverty, underinsurance, and less access to health care providers. In this study, we found relatively few significant differences across the 3 sites; children treated at the urban site showed evidence of greater health care utilization, including higher rates of hospitalizations and ED visits in the last year, as well as more frequent regular asthma appointments with their regular asthma care provider.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency department visits and hospitalisation for asthma seem to be related to several psychosocial factors, such as lower socioeconomic status [2], inaccessibility of medical care [2] and co-existing psychiatric diseases [3]. In addition, patient characteristics that are associated with severe life-threatening asthma attacks include female sex, older age, smoking and noncompliance with recommended therapy [4][5][6][7].…”
mentioning
confidence: 99%